CDC25B is required for the metaphase I-metaphase II transition in mouse oocytes - Ferencova, Ivana; Vaskovicova, Michaela; Drutovic, David; Knoblochova, Lucie; Macurek, Libor; Schultz, Richard M; Solc, Petr (Journal of cell science, 2022)
Mammalian oocytes are arrested at meiotic prophase I. The dual-specificity phosphatase CDC25B is essential for cyclin-dependent kinase 1 (CDK1) activation that drives resumption of meiosis. CDC25B reverses the inhibitory effect of the protein kinases WEE1 and MYT1 on CDK1 activation. Cdc25b-/- female mice are infertile because oocytes cannot activate CDK1. To identify a role for CDC25B following resumption of meiosis, we restored CDK1 activation in Cdc25b-/- oocytes by inhibiting WEE1 and MYT1, or expressing EGFP-CDC25A or constitutively active EGFP-CDK1 from microinjected complementary RNAs. Forced CDK1 activation in Cdc25b-/- oocytes allowed resumption of meiosis, but oocytes mostly arrested at metaphase I (MI) with intact spindles. Similarly, approximately a third of Cdc25b+/- oocytes with a reduced amount of CDC25B arrested in MI. MI-arrested Cdc25b-/- oocytes also displayed a transient decrease in CDK1 activity similar to Cdc25b+/+ oocytes during the MI-MII transition, whereas Cdc25b+/- oocytes exhibited only a partial anaphase-promoting complex/cyclosome activation and anaphase I entry. Thus, CDC25B is necessary for the resumption of meiosis and the MI-MII transition.
Keywords: CDC25B; oocyty; Mammals; Metaphase; anafázi podporující komplex; Mouse oocytes; Meiosis; Anaphase I; Anaphase-Promoting Complex-Cyclosome; savci; Resumption of meiosis; meióza; Animals; cdc25 Phosphatases; ženské pohlaví; anafáze; Meiotic maturation; Anaphase; zvířata; myši; metafáze; fosfatasy cdc25; Mice; Female; Oocytes